2012
DOI: 10.1038/nm.2682
|View full text |Cite
|
Sign up to set email alerts
|

2-hydroxyglutarate detection by magnetic resonance spectroscopy in IDH-mutated patients with gliomas

Abstract: Mutations in isocitrate dehydrogenase 1 and 2 (IDH1, 2) have been demonstrated in the majority of World Health Organization grade 2 and grade 3 gliomas in adults. These mutations are associated with the accumulation of 2-hydroxyglutarate (2HG) within the tumor. Here we report the noninvasive detection of 2HG by proton magnetic resonance spectroscopy (MRS). The pulse sequence was developed and optimized with numerical and phantom analyses for 2HG detection. The concentrations of 2HG were estimated using spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
671
1
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(706 citation statements)
references
References 30 publications
(44 reference statements)
9
671
1
8
Order By: Relevance
“…The short-echo MRS is widely available on clinical scanners, though the false-positive rate is approximately 22% [35]. There have been other, more complex MRS techniques that have been more successful, such as Choi et al [36], who identified all patients with IDH mutations without false-positive results. This compares to a sensitivity and specificity of 75 and 70% (AUC = 0.84) using median ADC alone.…”
Section: Discussionmentioning
confidence: 99%
“…The short-echo MRS is widely available on clinical scanners, though the false-positive rate is approximately 22% [35]. There have been other, more complex MRS techniques that have been more successful, such as Choi et al [36], who identified all patients with IDH mutations without false-positive results. This compares to a sensitivity and specificity of 75 and 70% (AUC = 0.84) using median ADC alone.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to positron emission tomography (PET) or hyperpolarized 13 C MRS, which require injections of radiolabelled tracers or large influxes of slowly relaxing stable isotopes, 1 H MRS utilizes endogenous brain metabolites at physiological concentrations and conditions as molecular reporters. Despite this ideal scenario, MRS is generally limited by the low sensitivity associated with metabolic concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For central nervous system (CNS) studies, in particular, endogenous metabolites could report on crucial events such as neurotransmission, pH, redox states, membrane synthesis and energetic turnover 10,11 . Metabolites could also serve as early reporters for neurological disorders such as dementia, schizophrenia, and Parkinson's and Huntington's diseases 12 , about the fate of malignancies 13 , and about ischaemic processes 7 . Magnetic resonance spectroscopy (MRS) is an ideal methodology to investigate these CNS metabolic aspects in vivo and noninvasively 14 .…”
mentioning
confidence: 99%
“…Alternative methods for parameter optimizations mostly aiming at specific metabolites have often been based on finding the best acquisition parameters for optimal target signal yield but also with minimal spectral overlap between the target and nuisance signals (Choi et al, 2010;Choi et al, 2012;Hu et al, 2007;Kim et al, 2005;Snyder and Wilman, 2010), usually based on quantum mechanical simulations and in vitro experiments. These investigations certainly have the advantage of yielding basic understanding of why certain parameter settings are optimal, but the CRBs inherently provide a tool that includes these optimization criteria and also extends them to other interfering metabolites and experimental factors.…”
Section: Discussionmentioning
confidence: 99%